Carbon sources of fish in an Amazonian floodplain lake - Oliveira, Ana Cristina B; Soares, Maria Gercilia Mota; Martinelli, Luiz Antônio; Moreira, Marcelo Z. (Aquatic Sciences, 2006)
In a tropical floodplain lake in central Amazon (L. Camaleão), we investigated seasonal shifts in primary carbon sources for commercially important fish species over an hydrological cycle. Carbon and nitrogen stable isotope and stomach content analyses were conducted to investigate the feeding preferences of six species with different feeding habits: Cichla monoculus (piscivorous species), Schizodon fasciatus (herbivorous), Prochilodus nigricans (detritivorous), and the omnivorous species Triportheus angulatus, Colossoma macropomum and Mylossoma duriventre. Stomach content and isotopic analyses exhibited a high seasonal variation for four out of the six species. The dominant food items were fruits and seeds, plant material, zooplankton and aquatic and terrestrial insects. Over the hydrological cycle, C3 plants were the major carbon source for all fish species. In addition, seston and aquatic C4 macrophytes were very important carbon sources for most species. Our findings underpin the complex trophic linkages between floodplain lakes and the aquatic terrestrial transition zone as postulated by the Flood Pulse Concept. © Eawag, 2006.
Keywords: Aquatic Organism; Carbon Budget; Feeding Behavior; Fish; Floodplain; Hydrological Cycle; Isotopic Analysis; Lake Ecosystem; Nitrogen Compound; Seasonal Variation; Stable Isotope; Stomach Content; Tropical Environment; Amazon River; South America; Cichla Monoculus; Colossoma Macropomum; Hexapoda; Insecta; Mylossoma Duriventre; Prochilodus Nigricans; Schizodon Fasciatus; Triportheus Angulatus